Emerging local authority networks within the framework of local administration reform in Hungary - Somlyódyné Pfeil, Edit (IGiPZ PAN, 2009)
Hungary is struggling with its fragmented local governmental system. The so called “public service reform” aimed to offer equal access to all as regards local public services, as well as to encourage efficiency of activity at local administrative level. The government transferred to local actors the responsibility for the implementation of reform commissioned centrally. The organisational and geographical frameworks for the rationalisation of local public administration were in turn devised at micro-regional level. This paper mainly aims to analyse urban-rural connections, as co-operative networks of local authorities have already been created. The issue is the extent to which the horizontal cooperations created to organise public services can be effective if their vertical connections are very weak, and, further, if there is no mechanism to counterbalance regional differences.
24 cm
Keywords: reforma administracji publicznej; spójność społeczna; spójność terytorialna; współpraca między miastami; usługi publiczne; efektywność

Cohesion of the European regional space - Proniewski, Marek (IGiPZ PAN, 2016)
The purpose of the EU cohesion policy is to reduce disparities at the level of economic, social and spatial development of the underdeveloped regions. The Europe 2020 Strategy establishesmore growth- and innovation-oriented investments. The main objective of this paper is to analyze and evaluate the differences and dynamics of the EU regions at the NUTS 2 level, characterized by the selected variables in the economic, social and territorial accessibility (transport infrastructure) area to determine the clusters of different levels of disparities in the EU regions (HDI) and transport infrastructure as well as to examine their interdependence. Calculations were based on statistical data acquired from Eurostat databases. The results confirm a distinctively clear inequality of economic development in the European regional space between Central and Eastern Europe as well as Northern and Western Europe regions, with the highest growth of dynamics identified in the regions of the countries that joined the EU in 2007 and 2004. The analysis also identifies the European regions with a high level of spatial cohesion (accessibility) and validates the thesis about the presence of interdependence between the EU regional development and spatial cohesion (accessibility) of the regions.
Każdy numer posiada własny tytuł.
Keywords: Unia Europejska; spójność gospodarcza; spójność społeczna; spójność przestrzenna; rozwój regionalny; HDI; infrastruktura transportowa

Panta rhei? Space of flows in the era of anthropocene and outlooks into a multi-coloured future - Meier-Dallach, Hans-Peter. Autor; Heinickel, Gunter. Autor (IGiPZ PAN, 2018)
The modern social, economic and communication flows change profoundly the development of spaces, their borders and boundaries, and affect the channels of flow between regions and the national, transnational and global society. The paper offers a reflection about the developments at the top of geographic and social scientific research as well as a reference to the agenda of spatial planning and politics. Therefore this article focuses on theoretical aspects of the “fluid society” but emphasizes also the need to learn from empirical insights and practical issues in the context of Polish-Swiss cooperation projects. It concludes however, that regional spaces under the auspices of modern flows are not unicoloured. That wants to say: they are not passive entities of modernisation, but keep their manifold, multicoloured characteristics – and these characteristics interact in the form of identities, cohesion and the natural backdrop with significant effects on those flows, enabling and steering modernisation strategies, and deciding about successes or failures of investments into traffic, tourism and economies. By that they shape the flows from and into peripheral regions.
29 cm
Każdy numer posiada własny tytuł.
Keywords: płynne społeczeństwo; rozwój regionalny; zróznicowanie kulturowe; tożsamość regionalna/lokalna; spójność społeczna; zmiany regresywne; strategie progresywne; rozwój cykliczny/transgresywny